Effect of Pigment Intensity and Region of Eggshell on the Spectral Transmission of Light That Passes the Eggshell of Chickens - Shafey, T.M.; Ghannam, M.M.; Al-Batshan, H.A.; Al-Ayed, M.S. (International Journal of Poultry Science, 2004)
The effects of intensity of brown pigment and region (small pole, equator and large pole) of eggshell on eggshell thickness and per cent transmittance of light (PT) that passes through the eggshell of chicken eggs were investigated. The PT was measured over the wavelength (WL) range of 200 to 800 nm (near-ultra violet (near-UV) WL range from 200 to 380 nm, visible (V) WL range from 380 to 780 nm and near-infra red (near-IR) WL range from 780 to 800 nm). Brown pigment eggshells [light (LBP), medium (MBP) and dark (DBP)] from meat-type breeder (Hybro) eggs of comparable weight were used. The intensity of brown pigment and region of eggshells did not affect eggshell thickness, but significantly (P<0.01) influenced the PT that passes through the eggshell over the WL range of 200 to 800 nm. LBP had higher PT and spectral transmission ratio of the near-UV:V and lower spectral transmission ratio of the near-IR:V when compared with those of the MBP and DBP. Whilst, the MBP had a higher PT than that of the DBP. The equator of eggshell transmitted more light when compared with those of the small (over the near-UV range) and large (over the WL range measured) poles regions. The small pole region of eggshell had higher PT and lower spectral transmission ratios of the near-UV:V and near-IR:V than those of the large pole region. There was an interaction between brown pigment and region of eggshell on PT of light. MBP and DBP eggshells have similar PT at the equator but differ at the poles regions of eggshells. In the MBP, the equator region of eggshell had a lower PT than that of the small pole. Whilst the equator region of the DBP had a higher PT than that of the large pole. The PT of the small pole was higher than that of the large pole in the LBP and DBP groups. It is concluded that the intensity of brown pigment and region of eggshell influence light transmission that passes through the eggshell and consequently the spectral characteristics of eggshell.